Identification of hydraulic fracturing impact factors on the skin effect in the near-wellbore zone of the reservoir - Kuper, Ivan; Mykhailyshyn, Bohdan; Lartseva, Iryna (Technology audit and production reserves, 2025)
The object of this research is the clogging of the near-wellbore zone of the productive reservoir, which leads to the formation of a positive skin factor and a decrease in well productivity. The subject of the study is the impact of hydraulic fracturing on the reservoir properties of the near-wellbore zone, as well as the assessment of the effectiveness of modern numerical modeling methods for predicting well productivity and optimizing technological parameters of production stimulation operations. The study addressed the problem of gas well productivity decline due to the deterioration of the filtration and capacitive properties of the near-wellbore zone of the formation caused by clogging, fluid accumulation, retrograde condensation and other physical and chemical processes that impede the movement of fluids to the bottomhole. The work is aimed at finding an effective stimulation method to increase well production and reduce the skin factor, as well as refining methods for forecasting production rate taking into account reservoir properties. In the course of identifying patterns, an injection test and regression analysis, software productivity modelling, and hydraulic fracturing of the X1 well. After fracturing, a significant increase in absolute free flow rate was recorded – from 1240 to 13250 m³/d. The numerical modelling performed before and after hydraulic fracturing allowed to optimize engineering solutions, reduce uncertainty in work planning and achieve high accuracy of the flow rate forecast. In the course of identifying patterns, the dependencies between fracture geometry, skin factor and flow rate were determined, which made it possible to quantify the effectiveness of hydraulic fracturing. A practically oriented approach to the implementation of well modelling was developed. The obtained results can be effectively used in the design and modelling of hydraulic fracturing in practice under conditions of clogging of the near-wellbore zone, positive skin factor, and low permeability of the formation, will significantly increase well production rates and the efficiency of reservoir development with complex filtration conditions.